Development of the Readiness for Hospital Discharge Scale for Patients with Bile Duct Carcinoma Catheterized After Percutaneous Transhepatic Cholangial Drainage: A Validity and Reliability Study - Zhao J; Ding W; Fan B; Chen C; Wang L (Dove Medical Press, 2024)
Jia Zhao,1,* Wenbin Ding,1,* Benfang Fan,2 Chunxia Chen,1 Lihua Wang2 1Department of Interventional Radiology, Nantong First People's Hospital, Nantong, 226001, People's Republic of China; 2Nursing Department, Nantong First People's Hospital, Nantong, 226001, People's Republic of China*These authors contributed equally to this workCorrespondence: Lihua Wang, Nursing Department, Nantong First People's Hospital, No. 666 of Shengli Road, Chongchuan District, Nantong, 226001, People's Republic of China, Tel +86 513 81111039, Email wanglihuawlh6@126.comObjective: We develop the Readiness for Hospital Discharge Scale (RHDS) for patients with bile duct carcinoma catheterized after percutaneous transhepatic cholangial drainage (PTCD) and test the reliability and validity of the scale, so as to provide a quantitative tool for evaluating the discharge readiness of patients catheterized after PTCD.Methods: The initial scale was developed following literature review, qualitative interviews, expert consultation, and other methods based on Meleis' Theory of Transition. We selected a total of 286 patients with bile duct carcinoma catheterized after PTCD from four tertiary A-grade hospitals in Nantong City. We conducted a cross-sectional survey using the initial scale to test the validity and reliability of the scale.Results: RHDS for patients catheterized post-PTCD consisted of five dimensions, with a cumulative variance contribution rate of 74.6%. The Cronbach's α coefficient of the scale was 0.856, and that of each dimension was between 0.740 and 0.891; the scale-content validity index (S-CVI) was 0.875.Conclusion: RHDS for patients with bile duct carcinoma catheterized after PTCD developed in this study, has good reliability and validity, and can be a useful tool for evaluating the discharge readiness of patients with bile duct carcinoma catheterized after PTCD.Keywords: bile duct carcinoma, discharge readiness, percutaneous transhepatic cholangial drainage, scale